(untitled) (Journal of Governance and Development (JGD), 2019)
The widespread usage of ICT provides considerable opportunities for the society. However, there is extensive evidence that through the use of ICTs students will be exposed to different e- safety challenges and risks. E-safety challenges faced through the use of internet and social media can be exposure to inappropriate content and communicating and meeting the strangers, cyber bullying, ICTsâ€™ addiction and cyber-harassment. Therefore, the aim of this action research is to develop a strategy to enhance e-safety among ï¬rst year students at Zimbabwe Universities. The overarching research strategy was action research using some qualitative research methods to gather the information on the e-safety uses, risks faced by students and how these risks can be mitigated. Data was collected using online questionnaire, group discussion, observation of ï¬rst students at Zimbabwean University. The research was iterative and there were two cycles done and the ï¬ndings culminated into a strategy being formed using the WHAT, WHO and HOW. This research contributes to the existing body of knowledge by providing a clear strategy to deal with e-safety challenges in Zimbabwean universities. Furthermore, this research is deemed to be signiï¬cant for understanding the future of ICT use in developing countries like Zimbabwe.